Evaluasi dan Audit Aplikasi Mobile JKN pada BPJS Kesehatan Menggunakan Model TAM dan COBIT 5.0 - Rizky Amalia; Wasilah; Rini Nurlistiani (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Mobile JKN is an application built by BPJS Kesehatan to use the current use of mobile technology. The JKN Mobile Application is expected to provide convenience for the public in accessing information related to the BPJS service program online. The importance of Mobile JKN services to carry out operational activities must be in optimal conditions. In fact, there are still many things that need to be related to JKN's mobile information technology. The low interest of the people of Bandar Lampung in using the Mobile JKN application. This is indicated by the queue of information request services that are always full at the BPJS office. This condition indicates the need for measuring application acceptance (acceptance) for the community, as well as evaluating the JKN mobile application. This study aims to measure the readiness of BPJS health users in Bandar Lampung to use the JKN BPJS mobile application and build recommendations for improving information technology governance related to the JKN BPJS mobile application. This study uses the TAM (Technology Acceptance Model) analysis model to determine Perceived Usefulness and Perceived Ease of Use, as well as the implementation of information system audits related to IT security risks using Control Objective for Information and Related Technology (COBIT). The results of the research value of benefit (PU) is 62% and convenience is 59%. As for the analysis of the JKN mobile application, the current maturity value and expected maturity are 1.03